Silicon application alleviates the effects of salt stress in sorghum and sunflower plants - Hurtado, Alexander Calero [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The effect of silicon (Si) on physiological and nutritional mechanisms to attenuate salt stress depends on the species and the mode of supply of the beneficial element. The objective of this study was evaluated whether supplied Si in different mods-manner attenuates the deleterious effects of salt stress based on the biochemical, physiological and nutritional responses of two distinct species, sorghum (accumulator of Si) and sunflower (intermediate accumulator of Si) under greenhouse conditions. Two pots experiments were carried out in a randomized block in a factorial scheme (2 × 4) with two factors, include salinity which was applied to the root medium as sodium chloride (NaCl), with the control and salt-stress groups (0 and 100 mmol L-1 NaCl), and the plants from each group were combined with the following Si-treatment groups: control (no Si), foliar application (28.6 mmol L-1), root application (2 mmol L-1), and combined foliar and root applications. Stabilized sodium and potassium silicate (SiNaKE) were used to maintain the Si levels. We tested the effects of different methods of Si applications in the response of mineral and water uptake, lipid peroxidation, proline concentration, enzymatic antioxidants activities, root diameter, leaf area, uptake and use efficiency of macronutrients and micronutrients in sorghum and sunflower plants under salinity stress conditions. Forty days after cultivation, in the stage S4 for sorghum and V8 for sunflower, the plants were harvested. Salinity stress decreased all the biological parameters. Si application resulted in higher K+ accumulation, and lower Na+ accumulation and lipid peroxidation levels in sorghum and sunflower leaves compared with untreated plants. In addition, Si increased the leaf relative water content, modified the proline content, enhanced enzymatic antioxidants activities, root diameter, leaf area, nutritional efficiency, and roots, shoots, and whole dry matter. These increases were more prominent under salinity stress, when Si was applied via nutrient solution in sorghum plants and the combined foliar and root applications of Si in sunflower plants. Our results also suggest that foliar Si spraying may be important in the biochemical and physiological activities for growth and development of both salt-stressed sorghum and sunflower plants.

O efeito do silício (Si) nos mecanismos fisiológicos e nutricionais para atenuar o estresse salino depende da espécie e do modo de suprimento do elemento benéfico. Em este estudo foi avaliado se o Si fornecido de diferentes modos atenua os efeitos deletérios do estresse salino com base nas respostas bioquímicas, fisiológicas e nutricionais de duas espécies distintas, sorgo (acumulador de Si) e girassol (acumulador intermediário de Si) em casa de vegetação. Dois experimentos para cada cultura foram realizados em blocos casualizados em esquema fatorial (2 × 4) tendo na solução nutritiva na ausência e na presença de 100 mmol L-1 NaCl e com fornecimento de Si em quatro formas diferentes: aplicação via foliar (28,6 mmol L-1), aplicação radicular (2 mmol L-1), aplicação foliar e radicular combinadas, e controle (sem Si). O Si foi utilizado na forma de silicato de sódio e potássio estabilizado (SiNaKE). Avaliaram-se o acúmulo de Si peroxidação lipídica, concentração de prolina, atividade enzimática antioxidante, diâmetro das raízes, área foliar, eficiências de absorção e uso dos macronutrientes e micronutrientes em plantas de sorgo e girassol. Aos quarenta dias após início dos tratamentos realizou-se a coleta das plantas no estágio S4 para sorgo e V8 para girassol. O estresse salino prejudicou todas as variáveis biológicos nas duas culturas. A aplicação de Si resultou em maiores acúmulos de K+ e diminuiu o acúmulo de Na+ e a peroxidação lipídica nas folhas de sorgo e de girassol em comparação com as plantas não tratadas. Além disso, o Si aumentou o conteúdo relativo da água nas folhas, modificou o conteúdo de prolina, aumentou a atividade das enzimas antioxidantes, diâmetro das raízes, área foliar, a eficiência nutricional e a massa seca das raízes, parte aérea e a planta inteira. Esses benefícios foram mais proeminentes sob salinidade, quando o Si foi aplicado via solução nutritiva em plantas de sorgo e a aplicação combinada de Si via foliar e radicular em plantas de girassol. Nossos resultados também sugerem que a aplicação foliar de Si pode ser importante nas atividades bioquímicas e fisiológicas beneficiando o crescimento e o desenvolvimento das plantas de sorgo e girassol estressadas por sal.
Aplicação de silício atenua os efeitos do estresse salino em plantas de sorgo e girassol
Keywords: Helianthus annuus; Sorghum bicolor; Beneficial element; Enzymatic activity; Nutritional efficiency; Oxidative stress; Proline; Salinity